APPLICATION OF THEORY OF PLANNED BEHAVIOR IN CONSUMERS’ PURCHASE DECISION OF CATS AND DOGS FOOD PRODUCTS - Pratama, Rendi Tegar; Yuliati, Elevita (ASEAN Marketing Journal, 2021)
Manuscript type: Empirical paper Research Aims: This research was conducted to analyze the influence of Theory of Planned Behaviour in determining the consumers’ purchase behaviour of cats and dogs food products. Design/methodology/approach: The constructs used in the research model are attitude, subjective norms, Perceived Behavioural Control (PBC), intention, and behaviour. The research model was added with self-identity and social norms constructs. Respondents of this research were 300 cats and dogs owners. Data was collected through online questionnaires. Data analysis was conducted using Structural Equation Modeling (SEM) with LISREL version 8.8 as the software analysis tool. Research Findings: The results showed that attitude, subjective norms, Perceived Behavioural Control (PBC), self-identity and social norms influenced the purchase intention of cats and dogs food products. In addition, the intention to buy cats and dogs food products also influenced consumers’ purchasing behaviour. Theoretical Contribution/Originality: This study supports the alignment of the theory of planned behaviour (TPB) to the marketing of dog and cat food products. Practitioner/Policy Implication: From the results obtained, there were some practical suggestions such as improving the attitude of the dog or cat owner by providing promotions. Research limitation/Implications: Some improvements in next research can be done by using other theories in consumer behaviour and develop a more extensive research model by adding variables or factors that can influence consumer behavioural intention in product purchases.